Exposure of Pleurotus sajor caju to UV light enhanced the nutritional yield of agricultural wastes - Adejumo, Isaac Oluseun; Adetunji, Charles Oluwaseun; Adeyemi, Oluyomi S. (Journal of Agricultural Sciences (Belgrade), 2017)
The wild and mutant strains of Pleurotus sajor caju was cultured on different agricultural substrates. Treatment 1 contained specific agricultural substrate waste alone. Treatment 2 contained the mutant strain of mushroom plus agricultural waste. Treatment 3 contained the wild strain of the mushroom plus agricultural waste. The mutant strain of Pleurotus sajor caju cultured on groundnut shell had the highest iron content while the mutant strain cultured on palm kernel meal had the highest biomass production, 10.5 g/L and 17.20 g/L after 7 and 14 days respectively. The proximate analyses of the feed variety (Mycomeat) revealed rich nutritional content which may be explored for feed ingredient in livestock production. The findings do not only support the bioremediation of agricultural waste to produce high-value bio-product but also provide evidence that improvement of microorganism strain represent a viable way to enhance nutritional value of fermented products.